If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 81 + -2(x + -1) * 2 = 51 Reorder the terms: 81 + -2(-1 + x) * 2 = 51 Reorder the terms for easier multiplication: 81 + -2 * 2(-1 + x) = 51 Multiply -2 * 2 81 + -4(-1 + x) = 51 81 + (-1 * -4 + x * -4) = 51 81 + (4 + -4x) = 51 Combine like terms: 81 + 4 = 85 85 + -4x = 51 Solving 85 + -4x = 51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-85' to each side of the equation. 85 + -85 + -4x = 51 + -85 Combine like terms: 85 + -85 = 0 0 + -4x = 51 + -85 -4x = 51 + -85 Combine like terms: 51 + -85 = -34 -4x = -34 Divide each side by '-4'. x = 8.5 Simplifying x = 8.5
| 3x^2-4=4-3x^2 | | -12x-9x=9x+24 | | 2x+5-15+3x=5 | | 6x(5x+3)=18x | | 5k-12=20 | | 2x+4(2x+4)=50 | | 8x-8=3x+4 | | 6x+80=9x-7 | | 12-7x=162-42x | | 129-9x=9x+15 | | 2*x*x+5=10 | | 9+.44444444444=19 | | 6x+83=9x-7 | | 2x^3-x^2-1=0 | | 2+45-3/2=12b | | 8t-5=19 | | 6x-11-7x+12= | | 4x^2-4x+4=0 | | -x^2+x-12=0 | | 4(y+3)=7-5y | | (19x-17)-(3x-72)=-13+(13x+83) | | 9-9x=84-44x | | (1x)(6x)+7x+12=0 | | 6x+2=5(x+1) | | 80-2x=4x-14 | | (6x)(6x)+7x+12=0 | | 6x-(8x-10)=87-(21+10x) | | 8n-25=39 | | 6x+26=14-46 | | 8z-6=11z-7 | | 6-8x=58-22x | | 3x+13=-11-9x |